Diversity-Oriented Synthesis and Chemoinformatic Analysis of the Molecular Diversity of sp3-Rich Morpholine Peptidomimetics - Lenci, Elena; Innocenti, Riccardo; Menchi, Gloria; Trabocchi, Andrea (Frontiers in Chemistry, 2018)
Diversity-Oriented Synthesis (DOS) consists of generating structurally diverse compounds from a complexity-generating reaction followed by cyclization steps and appendage diversity. DOS has gathered interest to systematically explore the chemical space by generating high-quality small-molecule collections as probes to investigate biological pathways. The generation of heterocycles using amino acid and sugar derivatives as building blocks is a powerful approach to access chemical and geometrical diversity thanks to the high number of stereocenters and the polyfunctionality of such compounds. Our efforts in this field are focused on the generation of diversity-oriented molecules of peptidomimetic nature as a tool addressing protein—protein interactions, taking advantage of amino acid- and sugar-derived polyfunctional building blocks to be applied in couple-pair synthetic approaches. In this paper, the combination of diversity-oriented synthesis and chemoinformatics analysis of chemical space and molecular diversity of heterocyclic peptidomimetics are reported, with particular interest towards carbohydrate- and amino acid-derived morpholine scaffolds with a higher fraction of sp3 carbon atoms. Also, the chemoinformatic analysis of chemical space and molecular diversity of such peptidomimetic scaffolds is outlined.